2020
DOI: 10.22219/jipt.v8i1.9841
|View full text |Cite
|
Sign up to set email alerts
|

Prediktor perundungan siswa sekolah dasar

Abstract: Abstrak. Perundungan merupakan persoalan serius yang memberikan dampak negatif bagi anak. Tujuan penelitian ini untuk mengeksplorasi prediktor perundungan siswa sekolah dasar di Kota Bandung. Hal ini penting agar dapat diketahui faktor-faktor yang berkontribusi dan meningkatkan peluang terjadinya perundungan pada siswa sekolah dasar. Dengan mengetahui prediktor tersebut, maka dapat dilakukan upaya pencegahan terjadinya perundungan. Sampel penelitian ini adalah 809 siswa sekolah dasar di Kota Bandung yang dipil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
1
7
0
10
Order By: Relevance
“…Teachers need to pay more attention to the possibilities of bullying incidents in the classroom, especially when the learning process is running in the classroom. Other studies showed that the prevalence of being mocking other students at school, raising the possibilities of bullying incidents happen in the classroom [33]. This is in line with these findings, where students might mocking other students in the class that then ended up being bullied.…”
Section: Resultssupporting
confidence: 77%
“…Teachers need to pay more attention to the possibilities of bullying incidents in the classroom, especially when the learning process is running in the classroom. Other studies showed that the prevalence of being mocking other students at school, raising the possibilities of bullying incidents happen in the classroom [33]. This is in line with these findings, where students might mocking other students in the class that then ended up being bullied.…”
Section: Resultssupporting
confidence: 77%
“…The Children's Worlds report showed that 27.1% of students were hit by other students at school, 36.7% of students were name-called by other students at school, and 26.5% of students were left out by other students in the class . Bullying incidents most frequently happen in elementary and middle school (Borualogo et al, 2020b;Fitzpatrick & Bussey, 2011). Therefore, the focus of this study was school bullying in elementary and middle school students.…”
mentioning
confidence: 99%
“…Parents are perceived as the source of main social support when children being victimised at school (Borualogo et al, 2020a). Parenting styles, as one of the microsystem components (Bronfenbrenner, 1986), is a predictor of school bullying (Borualogo et al, 2020b). Parenting styles and communication between parents and children correlated with children involvement in bullying, whether as the perpetrator and as the victim (Georgiou, 2008;Georgiou & Stavrinides, 2008;Lereya et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a meta-analysis, Lee et al (2013) found that including an anti-bullying school policy was one of the elements that worked to help the program achieve success. A study in Indonesia also shows that parents are a significant predictor of children's involvement in bullying (Borualogo et al, 2020b).…”
Section: Developing the Intervention Programmentioning
confidence: 98%